Analysis of Students' Conceptual Understanding Ability and Learning Independence Reviewed From Students' Learning Motivation Assisted by Macromedia Flash in Class X of SMA Kesatuan Meranti - Umami, Reza (Study Program of Mathematics Education of Unimed Postgraduate Program, 2024)
This research aims to: (1) To find out whether there is a difference in students' ability to understand concepts between students who were given Macromedia Flash media and students who were given Power Point media (2) To find out whether there is a difference in students' independent learning abilities between students who were given Macromedia Flash media. with students who were given power point media. This type of research is a quasi experiment. This research was carried out in SMA Kesatuan Meranti in the even semester of the 2021/2022 academic year. The results of the research show that: 1) There is a difference in students' ability to understand concepts between students who were given Macromedia Flash media and Power Point media, where the application of Macromedia Flash media was better than students who received Power Point media for their ability to understand concepts; 2) There is a difference in students' independent learning abilities between students who were given Macromedia Flash media and Power Point media, where the application of Macromedia Flash media was better than students who received Power Point media for students' independent learning abilities; 3) There is an interaction between learning media and student learning motivation which is used on students' ability to understand concepts; 4) There is no interaction between learning media and student learning motivation which is used on students' independent learning abilities.